Edward M. Kennedy : a biography - Clymer, Adam (1999)
"The life of Edward M. Kennedy is a chronicle of our country's past forty years - and this biography offers unprecedented insight into the many events of our times. Adam Clymer of The New York Times has followed Senator Kennedy through his high and lows to his present years as patriarch of the Kennedy family. Edward M. Kennedy focuses squarely on the Senator's career, addressing the difficulties he has encountered with personal matters but studying the influence his work has had in a broader context." "The list of Senator Kennedy's accomplishments includes his roles in the nuclear freeze, fighting for the rights of the disabled, helping to end apartheid in South Africa, and, most recently, the minimum wage increase and the Family Leave Act. These political victories speak for themselves, yet it is his personal life that has drawn as much attention. From Chappaquiddick to his public divorce to his involvement in his nephew William Kennedy Smith's Palm Beach incident, he has struggled to maintain his own dignity and that of his very visible family."--Jacket
ch. 1. Decision for 1984 -- ch. 2. Born to a dynasty -- ch. 3. Apprentice -- ch. 4. President's brother -- ch. 5. Crash -- ch. 6. Lawmaker -- ch. 7. To Vietnam and back -- ch. 8. Alliances and coalitions -- ch. 9. Last brother -- ch. 10. Summer of entreaties -- ch. 11. Leader with Robert's causes -- ch. 12. Chappaquiddick -- ch. 13. Staff to lean on -- ch. 14. Victory and defeat -- ch. 15. Investigations by and of Nixon -- ch. 16. Crisis at home -- ch. 17. No campaign in 1976 -- ch. 18. Unconventional wisdom -- ch. 19. Crime and taxes -- ch. 20. Strains with Carter, strains on Joan -- ch. 21. Beijing and Moscow -- ch. 22. Against the wind -- ch. 23. Losing -- ch. 24. In the minority, leading -- ch. 25. Little mud and Central America -- ch. 26. Pilgrimage to South Africa -- ch. 27. Advocate for arms control -- ch. 28. Defeating Bork -- ch. 29. Picking up his brothers' mantle -- ch. 30. Rights for the disabled -- ch. 31. Battles in the Senate and the Gulf -- ch. 32. Turning point -- ch. 33. President and an ally -- ch. 34. Still campaigning -- ch. 35. Counterrevolution -- ch. 36. Health care, bit by bit -- ch. 37. Job you asked the people for
Includes bibliographical references (pages 663-667) and index
Keywords: Kennedy, Edward M. -- 1932-2009; United States. -- Congress. -- Senate -- Biography; Legislators -- United States -- Biography; Biography